Primary cutaneous apocrine carcinoma of the scalp: Two case reports and literature review. Issue 6 (11th February 2022) - Choi, Jun Ho; Oh, Hyun Myung; Kim, Kwang Seog; Choi, Yoo Duk; Joo, Sung Pil; Hwang, Won Joo; Hwang, Jae Ha; Lee, Sam Yong
Abstract: Rationale: Apocrine carcinoma is a rare malignant sweat gland tumor that has been reported in approximately 200 cases. This tumor usually occurs in the axilla, but in rare cases, it can also develop in the scalp. In the present work, we report 2 cases of cutaneous apocrine carcinoma of the scalp. Patient concerns: Two men visited our outpatient clinic with recurrence of tumor after undergoing surgery for scalp tumor at another hospital. Diagnoses: Brain magnetic resonance imaging of a 56-year old man showed the presence of a 5.0 × 4.5 × 4.4 cm scalp mass in the right parietal region, invading the skull and dura mater and a 2.2 × 2.0 × 0.7 cm bony mass without any skin lesions right next to the scalp mass. Neck magnetic resonance imaging of a 76-year-old man revealed the presence of a well-defined oval mass in the subcutaneous layer of the left occipital scalp and 2 enlarged lymph nodes in the left neck. Definite diagnoses were made postoperatively. The patients were diagnosed with cutaneous apocrine carcinoma. The diagnosis was confirmed through histopathological and immunohistochemical staining tests. Interventions: The tumors were removed with a wide safety margin and reconstructive surgery was performed. Outcomes: Additional radiotherapy or chemotherapy was performed. Follow-up more than 6 months revealed no recurrence or metastasis. Lessons: If accurate diagnosis and treatment had taken place at the initial stages of the primary cutaneous apocrine carcinoma, it would have been possible to prevent recurrence and intracranial invasion. As recurrent primary cutaneous apocrine carcinoma can become aggressive and difficult to treat, even a small mass on the scalp must be evaluated carefully and treated properly.